Evaluation of a poly-herbal preparation for the treatment of peptic ulcer (Bangladesh Journal of Pharmacology, 2017)
The aim of this study was to validate the traditional uses of ulcerene, a poly-herbal formulation in ethanol, aspirin and stress-induced gastric ulcer model of rat. The extent of gastric ulcer formation was studied, using ulcer score, ulcer index, percentage cure through gross examination and histopathological evaluation. A significant (p